Legal Pluralism and the Enforcement of Zina Offences: Analysis of Customary and Jinayat Law in the Alas Community, Aceh - Nur Mala Sari; Febiawan Suparman Mustar; Abdul Manan; Jailani Jailani; Cut Maya Aprita Sari (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study analyzes the enforcement of adultery in the Alas Tribe community in Southeast Aceh Regency, highlighting the dominance of customary law mechanisms over formal law enforcement, as provided in Qanun Aceh Number 6 of 2014 concerning Jinayat Law. Although the qanun normatively regulates criminal sanctions for adultery, its implementation at the local level has not been effective. This study uses a normative-empirical approach, combining analyses of legislation, case studies, and in-depth interviews with traditional leaders, Wilayatul Hisbah officials, and Sharia Court judges. The results show a dualism in the mechanisms for resolving adultery cases, characterized by a strong community preference for customary law. Customary-based resolution is seen as better at maintaining family honor and restoring social harmony, but it also undermines legal certainty and the effectiveness of criminal punishment. This article argues that the dominance of customary mechanisms reflects the failure of normative integration between jinayat law and customary law, resulting in the inability to achieve the objectives of Islamic criminal punishment (maqāṣid al-'uqūbāt), particularly the deterrent effect, justice, and equality before the law. This research contributes to the development of Islamic legal pluralism studies by emphasizing the importance of functional integration between customary law and Islamic criminal law within indigenous Muslim communities.